The use of circuit simulators for array-pattern modeling and optimization. - McDonald, Noel
The purpose of this note is to describe the use of circuit simulators for the modeling, display and optimization of antenna array patterns. A particularly useful feature of such programs is the optimization facility. The examples given here are based on HP EEsof's Touchstone, which the author has used previously for this purpose, but other packages probably have similar features. Only a summary of the technique is given, and some familiarity with array theory and circuit simulators is assumed.
Keywords: Antenna radiation patterns; Optimization methods; Circuit simulation; Antenna arrays